Diarrheagenic Escherichia coli signaling and interactions with host innate immunity and intestinal microbiota - Wang, Gaochan (Kansas State University, 2017)
Diarrheagenic Escherichia coli (E. coli) strains are common etiological agents of diarrhea. Diarrheagenic E. coli are classified into enterotoxigenic E. coli (ETEC), Shiga toxin-producing E. coli (STEC or enterohemorrhagic E. coli [EHEC]), enteropathogenic E. coli (EPEC), enteroinvasive E. coli (EIEC), enteroaggregative E. coli (EAEC), diffuse-adherent E. coli (DAEC), and adherent invasive E. coli (AIEC). In addition to encoding toxins that cause diarrhea, diarrheagenic E. coli have evolved numerous strategies to interfere with host defenses. In the first project, we identified an ETEC-secreted factor (ESF) that blocked TNF-induced NF-[kappa]B activation. One of the consequences of TNF-induced NF-[kappa]B activation is the production of pro-inflammatory cytokines that help to eliminate pathogens. Modulation of NF-[kappa]B signaling may promote ETEC colonization of the host small intestine. In this study, we fractionated ETEC supernatants and identified flagellin as necessary and sufficient for blocking the degradation of the NF-[kappa]B inhibitor I[kappa]B[alpha] in response to TNF[alpha]. In the second project, we attempted to identify an ETEC cAMP importer. ETEC diarrhea leads to cAMP release into the lumen of the small intestine. cAMP is a key secondary messenger that regulates ETEC adhesin expression. We hypothesized that a cAMP importer is present in ETEC, accounting for its hypersensitivity to extracellular cAMP. We used Tn5 transposome-mediated mutagenesis to construct a mutant library and screen for cAMP-hyporesponsive mutants. However, none of the 17,956 mutants we screened were cAMP-hyporesponsive. In the third project, we focused on gut microbiota and the T3SS effector NleH. We used the mouse-specific pathogen C. rodentium and transplanted performed microbiota between different mouse strains. We evaluated microbiota populations as a function of infection with WT and [Delta]nleH C. rodentium strains before and after microbiota transplantation. Microbiota transfer altered the resistance to WT C. rodentium infection in C57BL/10ScNJ mice and the NleH effector promoted host resistance to C. rodentium.
Keywords: Diarrheagenic E. coli; NF-kappaB; flagellin; Microbiota; cyclin AMP; T3SS effector